2011
DOI: 10.1111/j.1462-2920.2011.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and dynamics of the gill microbiota of an invasive Indo‐Pacific oyster in the eastern Mediterranean Sea

Abstract: Gill bacterial communities of Chama pacifica, an Indo-Pacific invasive oyster to the eastern Mediterranean Sea, were compared with those of Chama savignyi, its northern Red Sea congeneric species. Summer and winter bacterial populations were characterized and compared using 16S rDNA clone libraries, and seasonal population dynamics were monitored by automated ribosomal intergenic spacer analysis (ARISA). Clone libraries revealed a specific clade of bacteria, closely related to marine endosymbionts from the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 42 publications
(41 reference statements)
7
59
0
Order By: Relevance
“…Numerous cultureindependent studies of marine invertebrates have shown similar dominance of members of Endozoicomonas (often incorrectly referred to as the uncharacterized genus 'Spongiobacter' or simply referred to as gammaproteobacteria clones) (e.g. Bellantuono et al, 2012;Bourne & Munn, 2005;Bourne et al, 2008;Cooney et al, 2002;Hansson et al, 2009;Jackson et al, 2012;Kennedy et al, 2008;Kvennefors et al, 2010;Lee et al, 2012;Littman et al, 2009;Lopez et al, 2008;Menezes et al, 2010;Morrow et al, 2012;Pike et al, 2012;Rohwer et al, 2001;Schuett et al, 2007;Zurel et al, 2011). Previous studies have demonstrated that coralassociated Endozoicomonas strains probably contribute to the degradation of sulfur compounds [e.g.…”
Section: Rheinheimera Baltica Osbac1 T (Aj441080)mentioning
confidence: 99%
“…Numerous cultureindependent studies of marine invertebrates have shown similar dominance of members of Endozoicomonas (often incorrectly referred to as the uncharacterized genus 'Spongiobacter' or simply referred to as gammaproteobacteria clones) (e.g. Bellantuono et al, 2012;Bourne & Munn, 2005;Bourne et al, 2008;Cooney et al, 2002;Hansson et al, 2009;Jackson et al, 2012;Kennedy et al, 2008;Kvennefors et al, 2010;Lee et al, 2012;Littman et al, 2009;Lopez et al, 2008;Menezes et al, 2010;Morrow et al, 2012;Pike et al, 2012;Rohwer et al, 2001;Schuett et al, 2007;Zurel et al, 2011). Previous studies have demonstrated that coralassociated Endozoicomonas strains probably contribute to the degradation of sulfur compounds [e.g.…”
Section: Rheinheimera Baltica Osbac1 T (Aj441080)mentioning
confidence: 99%
“…Similar studies regarding host-associated microbiota are almost exclusively limited to humans, (e.g., Caporaso et al, 2011; David et al, 2014; DiGiulio et al, 2015), and a handful of model organisms (e.g., Fink et al, 2013; Marino et al, 2014). Whereas temporal patterns have been studied in non-model organisms, the focus remains on the population level and the sampling resolution usually coincides with significant host/environment-related shifts: developmental (e.g., Trabal et al, 2012; Hroncova et al, 2015), seasonal (e.g., Zurel et al, 2011; Bjork et al, 2013; Ransome et al, 2014) or abiotic disturbances (e.g., Vega Thurber et al, 2009; Wegner et al, 2013; Tracy et al, 2015). Longitudinal, individual-based, repeated-measure studies remain scarce (but see Pratte et al, 2015; Glasl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities residing in different organs of several oyster species have only recently been described by using molecular, culture independent techniques [15-17] that allow intra- and interspecies comparisons [18] and the exploration of environmental factors, such as temperature [19]. For example, oysters invading the Mediterranean from the Indian ocean maintained some of their associated microbes throughout the invasion process [18].…”
Section: Introductionmentioning
confidence: 99%